ANALISIS PENGARUH PROFESSIONALISME TERHADAP KOMITMEN ORGANISASI, KEPUASAN KERJA, PRESTASI KERJA DAN KEINGINAN BERPINDAH BAGI TENAGA PROFESI PERAWAT (Studi Pada Rumah Sakit Islam Sultan Agung Semarang) - Rahayuningsih, Sri (Proceeding Fakultas Ekonomi, 2012)
This research aimed to test and analyze the influence of the profesionalism toward organizational commitment, working satisfaction, working achievement, and quitting pretention from the nurse of Sultan Agung Islamic Hospital. This research was done using survey method to 120 nurse of Islamic Hospital Sultan Agung  Semarang. Sampling technique used was census method. To test tha data, the writer use validity test through factor analysis, reliability test with Alpha Cronbach, classis assumption test, simple linear regression analysis, and t-test to test and prove research hypothesis. The validity of data collected was tested using factor analysis method and for its reliability was tested using alpha coefficient (Alpha Cronbach). The result  was that all data were valid and reliable. The result of analysis and disscussion showed that : (1) Professionalism positively influenced organizational commitment. It means that the higher professionalism the higher organizational commitment also; (2) Professionalisme positively influenced working satisfaction. It means that the higher ptofessionalism, the higgher working satisfaction alsol (3) Professionalisme positively influenced working achievement. It means that the higher ptofessionalism, the higgher  working achievement, also.  Professionalisme positively influenced quitting pretention. It means that the higher professionalism, the higgher quitting pretention  alsol Keywords: Profesionalism, Organizational Commitment, Working Satifaction, Working Achievement, and Quitting Prettention